Media Jejaring Pikiran Berbasis Pengalaman Pribadi dalam Pembelajaran Keterampilan Menulis Teks Cerpen untuk Mendukung Variasi Diksi - Rahmawati, Gemina; Umaya, Nazlah Maharani (Universitas Khairun, 2024)
This research aims to explore the methods of writing short stories in various dictions, the factors that cause a lack of ability to write short story texts, the innovative media used, and the benefits obtained by students in improving their short story writing. The research method was applied using data collection techniques through observation and literature study. From the research results, it was concluded that factors such as monotonous learning, difficulties in developing ideas, and a lack of understanding of the structure of short story texts can be the cause of the lack of ability to write short story texts, especially in class XI students at SMA N 9 Semarang. Innovative and effective media that can be applied using mind mapping. The application of this media is effective in supporting writing short story texts. The use of media has become closely associated with students through the Canva application, which uses a network of thoughts. It is hoped that it can overcome boredom when taking notes, making it easier for the brain to process, memorize and develop the information that has been recorded. By using the thought networking process, students can develop and expand ideas and thoughts before starting to write a short story, so that they can design an interesting story framework. However, the results of observations show that students have not been able to write a comprehensive, more structured and directed structure.